Central anticholinergic syndrome following reversal of neuromuscular blockade in a neonate. Issue 2 (8th October 2015) - Selvamani, Breethaa Janani; Hussain, Aftab; Rahman, Faizur; Fatima, Nida
Summary: Central anticholinergic syndrome (CAS) is rare in neonates. We report a case in a 10‐day‐old baby weighing 2.5 kg, following reversal of neuromuscular blockade using 0.1 mg atropine and 120 μg neostigmine. The use of atropine in 0.01‐0.02 mg.kg ‐1 dose rather than the recommended minimum dose of 0.1 mg may have prevented this complication.